Genomic Characterization of Laodelphax striatellus Permutotetra-like Virus and Self-Cleavage Function of Viral Capsid Protein - Jun Piao; Jiarui Zhang; Lujie Zhang; Jingai Piao; Haitao Wang; Yilin Xie; Shuo Li (Microbiology Research)
Laodelphax striatellus permutotetra-like virus (LsPLV) is a novel insect virus identified via small RNA deep sequencing. At present, there is a lack of awareness of LsPLV, restricting research on its utilization in biocontrol. In this paper, the full-length genome of LsPLV was cloned and analyzed, then viral capsid protein (CP) was expressed and prepared as an antibody, and CP property was tested. It was found that the LsPLV genome was 4667 nt in length, encoding two proteins, RNA-dependent RNA polymerase (RdRP) and CP, and the palm subdomain conserved region in RdRp was arranged in a “C–A–B” permutation pattern, exhibiting the typical characteristics of permutotetra-like viruses. Phylogenetic analysis suggested that LsPLV shared the highest homology (excluding LsPLV1) with a Nodaviridae virus (QLI47702.1), and their nucleotide identities of RdRP and CP were 55.4% and 59.2%, respectively. After expression, purified CP exhibited two bands of 60 kDa and 47 kDa, suggesting a potential cleavage in the protein. LsPLV CP in L. striatellus was detected by Western blot, and except for the complete CP band, the specific bands with molecular weights lower than CP were also detected, indicating that CP underwent cleavage. Detection of purified CP in vitro showed that the cleavage could occur independent of any protease, confirming that CP has self-cleavage characteristics.